Peran Organizational Commitment terhadap Hubungan Work-Family Conflict dan Kepuasan Kerja Karyawan Wanita di Kota Seribu Industri Tangerang - Teguh Yuwono; Dewiana Novitasari; Didi Sutardi; Mustofa Mustofa; Masduki Asbari (Universitas Muhammadiyah Enrekang, 2020)
This study aimed to measure the effect of work-family conflict on job satisfaction through organizational commitment (affective, continuence, normative) as mediation. Data collection was done by simple random sampling to 215 population of woman employee in a packaging industry in Tangerang. The returned and valid questionnaire results were 170 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that work-family conflict have not significant effect on job satisfaction, work-family conflict have significant effect on organizational commitment (affective, continuence, normative), and organizational commitment (continuence and normative) have mediating effect on relationship between work-family conflict and job satisfaction, except affective commitment have not significant effect on job satisfaction. This new research proposed a model for building job satisfaction among woman employee of packaging industry in Tangerang through enhancing organizational commitment and by manage the work-family conflict. This research could pave the way to improve woman employee readiness in facing the era of industrial revolution 4.0.